The FTO gene and obesity in a large Eastern European population sample: the HAPIEE study - Hubacek, Jaroslav A; Bohuslavova, Romana; Kuthanova, Lada; Kubinova, Ruzena; Peasey, Anne; Pikhart, Hynek; Marmot, Michael G; Bobak, Martin (Obesity (Silver Spring, Md.), 2008)
Variants in the FTO (oxoglutarate-dependent nucleic acid demethylase) gene have been associated with the BMI determination in Western European and North American populations. To widen the geographical coverage of the FTO studies, we have analyzed the association between the FTO gene variant rs17817449 (G>C) and obesity in a Slavic Eastern European population. A total of 3,079 males and 3,602 females 45-69 years old were randomly selected from population registers of seven Czech cities. We examined three indices of obesity: BMI (kg/m(2)), waist circumference, and waist-to-hip ratio (WHR). The FTO rs17817449 variant was significantly associated with BMI both in males (GG 28.7 +/- 4.1; GT 28.3 +/- 3.9; TT 28.0 +/- 3.9; P = 0.003) and females (GG 28.7 +/- 5.2; GT 28.2 +/- 5.1; TT 27.2 +/- 4.9; P < 0.001); the associations were not affected by adjustment for age, smoking, socioeconomic status, and physical activity. The FTO variant was also associated with waist circumference (difference between GG and TT was 1.1 cm (P = 0.043) in men and 2.4 cm (P < 0.001) in women) but this relationship disappeared after adjustment for BMI. Similarly, BMI explained the weak association of FTO with WHR and C-reactive protein. FTO was not associated with plasma total and high-density lipoprotein cholesterol, triglycerides, blood glucose, and blood pressure. These results confirm that in a Slavic population the FTO variant is strongly associated with BMI but not with other risk factors.
Keywords: Female; Waist-Hip Ratio; C-Reactive Protein; ženské pohlaví; obvod pasu; Obesity; diabetes mellitus; lidé; poměr pasu a boků; Proteins; Waist Circumference; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; proteiny; obezita; Male; Aged; Czech Republic; index tělesné hmotnosti; Česká republika; Diabetes Mellitus; lidé středního věku; C-reaktivní protein; senioři; gen pro FTO; mužské pohlaví; Body Mass Index; Middle Aged; Humans